Risk reduction using trailing stop‐loss rules. (11th August 2020) - Dai, Bochuan; Marshall, Ben R.; Nguyen, Nhut H.; Visaltanachoti, Nuttawat
Abstract: We consider the effectiveness of trailing stop‐loss rules which, unlike traditional stop‐loss rules, involve the sale trigger price being moved higher to protect profits as prices rise. Our results indicate that while these rules have inferior mean returns to a mean–variance optimal benchmark, they are effective at stopping losses. The trailing stop‐loss strategy reduces total risk and lessens downside risk, especially during declining market states. Transaction costs reduce the benefits of tighter stop‐loss rules, but the rules with larger stop‐loss thresholds remain useful after accounting for transaction costs.